Anatomical Correlates of Uncontrollable Laughter With Unilateral Subthalamic Deep Brain Stimulation in Parkinson’s Disease - Huang, Yonglu; Aronson, Joshua P.; Pilitsis, Julie G.; Gee, Lucy; Durphy, Jennifer; Molho, Eric Steven; Ramirez-Zamora, Adolfo (Frontiers in Neurology, 2018)
Introduction: Subthalamic nucleus deep brain stimulation (STN-DBS) is a well-established treatment for the management of motor complications in Parkinson’s disease (PD). Uncontrollable laughter has been reported as a rare side effect of STN stimulation. The precise mechanism responsible for this unique phenomenon remains unclear. We examined in detail the DBS electrode position and stimulation parameters in two patients with uncontrollable laughter during programming after STN-DBS surgery and illustrated the anatomical correlates of the acute mood changes with STN stimulation. Case report: Unilateral STN-DBS induced uncontrollable laughter with activation of the most ventral contacts in both patients. However, the location of the electrodes responsible for this adverse effect differed between the patients. In the first patient, the DBS lead was placed more inferiorly and medially within the STN. In the second patient, the DBS lead was implanted more anteriorly and inferiorly than initially planned at the level of the substantia nigra reticulata (SNr). Conclusions: Unilateral STN-DBS can induce acute uncontrollable laughter with activation of electrodes located more anterior, medial and inferior in relationship with the standard stereotactic STN target. We suggest that simulation of ventral and medial STN, surrounding limbic structures or the SNr are the most plausible anatomical substrate responsible for this acute mood and behavioral change. Our findings provide insight into the complex functional neuroanatomical relationship of the STN and adjacent structures important for mood and behavior. DBS programming with more dorsal and lateral contacts within the STN should be entertained to minimize the emotional side effects.